Remineralization potential of dentifrices with calcium sodium phosphosilicate and functionalized tri‐calcium phosphate in the deeper incipient carious lesions: An in vitro study - Shafiq Aziz; Carolina Loch; Kai Chun Li; Robert Anthonappa; Alison Meldrum; Manikandan Ekambaram (Wiley, 2024)
Abstract Objectives This study evaluated the remineralization potential of calcium sodium phosphosilicate and functionalized tri‐calcium phosphate (f‐TCP) dentifrices in deeper incipient carious lesions (ICLs). Materials and Methods Artificial ICLs were created by placing premolars into demineralizing solutions. Teeth were randomly assigned into four groups: calcium sodium phosphosilicate (Group 1), f‐TCP (Group 2), 1450 ppm fluoride (Group 3), and distilled water (Group 4), which were subjected to 10‐day pH cycling. Mineral density (MD) was assessed using microcomputed tomography (Micro‐CT), while hardness (H) and elastic modulus (EM) were assessed using nanomechanical testing. Results MD % gain was higher in Groups 1-3 than in Group 4. In addition, Groups 1 and 2 exhibited significantly higher MD % gain than Group 3. Also, Groups 1-3 showed significantly higher EM and H values than Group 4 in the outer enamel area; yet, Groups 1 and 2 displayed significantly higher EM and H values than Groups 3 and 4 in the inner enamel. Conclusions The MD, EM, and H of ICLs significantly increased with the addition of calcium sodium phosphosilicate or f‐TCP to fluoridated dentifrices compared to standard fluoride dentifrices. The added active ingredients remineralized the deeper parts of the ICLs, while remineralization at the lesion surface was similar between tested dentifrices.